Welcome to Night Vale - Fink, Joseph (Fiction writer); Cranor, Jeffrey, 1975- (HarperCollins, 2015)
Handed a message by a mysterious man, young pawn shop owner Jackie Fierro embarks on a psychologically dangerous mystery that entangles her in the life of Diane Clayton, the local PTA treasurer, who helplessly watches her son's growing obsession with his absent father.